Pemahaman Konsep IPS pada Materi Keberagaman Budaya Kelas IV SD Negeri 196 Palembang - Amelia, Kiki Rizky; Junaedi, Arvan; Syaflin, Sylvia Lara (Indonesian Research Journal on Education, 2023)
Concept understanding is an ability to think in processing material that has been received withseveral stages including absorbing, understanding, and accepting an idea then processed based onlearning experiences so that it is more meaningful. Therefore, to understand a concept, one mustunderstand several stages such as understanding and accepting a thought which is then processedbased on the learning experience. The purpose of this study was to find out the understanding ofsocial studies concepts in cultural diversity in the fourth grade of SD Negeri 196 Palembang. Theresearch method used in this research is descriptive qualitative. The data obtained were analyzedusing percentages. The results of this study indicate that the understanding of the social studiesconcept in the fourth grade material on cultural diversity at SD Negeri 196 Palembang is in agood category, this can be obtained through the collection of observational data, interviews anddocumentation.